Barriers and Strategies in Implementing Innovative and Collaborative Learning: A Case of Indonesian English Language Teaching - Bachtiar, Bachtiar; Puspitasari, Maya (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
Current educational theories and studies emphasize the need to use innovative and collaborative approaches to improve student’s learning experience, especially in the field of English Language Teaching (ELT). This study explores the obstacles and strategies for using these teaching approaches in the Indonesian ELT context. The research used mixed methods with a convergent parallel design. The questionnaires were used to gather data from 42 English as a Foreign Language (EFL) teachers, while semi-structured interviews were done with 6 teachers to explore their perspectives and experiences. The research was conducted in one district in West Sulawesi, Indonesia. The significant findings emphasize the critical impact of innovative and collaborative learning on improving students’ learning outcomes. The results also found obstacles that impede innovative and collaborative actual use, such as inadequate resources, teacher reluctance, and lack of appropriate teacher professional development. This research has potential implications beyond Indonesia and provides significant insights and suggestions for educators, policymakers, and stakeholders in comparable EFL situations globally to promote creative and collaborative learning environments.